Composition of Coronal Hole Boundary Layers at Low Heliographic Latitudes. Issue 8 (12th August 2021) - Delano, K.; Elliott, H. A.; Lepri, S. T.; Fuselier, S. A.
Abstract: In some polar coronal holes, previous studies have identified a coronal hole boundary layer (CHBL), which is different in composition from the coronal hole core region. However, compositionally distinct CHBL structure at low heliographic latitudes remains underexplored. Using solar wind composition measurements from the Advanced Composition Explorer (ACE), we study two particular low‐latitude coronal holes of 2003: a large polar hole extension with outward magnetic polarity and a smaller equatorial hole with inward magnetic polarity. For both of these coronal holes, we examine the distribution of two composition parameters, the O 7+ to O 6+ charge state density ratio (n(O 7+ )/n(O 6+ )) and the Fe to O abundance ratio (n(Fe)/n(O)), and find that each hole has an identifiable CHBL based on an anticorrelation of solar wind speed and n(O 7+ )/n(O 6+ ). We also examine the FIP (first ionization potential) effect in the CHBL using n(Fe)/n(O), and find that there is no significant change from the CHBL to the core region for one of the coronal holes we study, while the other coronal hole has a noticeable decrease in n(Fe)/n(O) values in its core. Finally, we discuss our results in the context of previous work studying CHBL structure. Key Points: Advanced Composition Explorer composition measurements indicate that the largest coronal hole extension of 2003 has a thick coronal hole boundary layer (CHBL) distinct from its core A CHBL is also observed in a small, inward‐polarity coronal hole in 2003; its speed range is not as broad as that of the largest extension In both coronal holes examined in this work, no change in the FIP effect is observed from the core to the CHBL